Characterization of an antigen from Leishmania amazonensis amastigotes able to elicit protective responses in a murine model. - Beyrodt, C G (1997)
Lymphoproliferative responses to an antigen from Leishmania amazonensis amastigotes with an apparent molecular mass of 30 kDa, termed p30, were evaluated with BALB/c mice. The p30 antigen was purified after separation of parasite extracts by sodium dodecyl sulfate-polyacrylamide gel electrophoresis followed by electroelution. Lymphoproliferative responses to p30 were obtained by subcutaneous immunization of animals with L. amazonensis amastigote extracts, and maximal stimulation indices were observed at an antigen concentration of 5 microg/ml. Induction of lymphoproliferation by p30 is stage specific, and no differences in the responses to this antigen between mice susceptible and resistant to L. amazonensis were detected. The predominant T cells characterized in the lymphocyte cultures were CD4+. Lymphokine analysis of the supernatants from these cultures indicated that Th1 is the subset involved in the lymphoproliferative responses to the antigen. BALB/c mice immunized with p30 and challenged with L. amazonensis amastigotes showed a very low level of infection, indicating a protective role for p30 and a correlation between Th1 and protection. Further biochemical characterization studies showed that this antigen presents cysteine proteinase activity.